Ética con responsabilidad social en la gestión pública y privada. Un cambio inaplazable bajo la norma SGE: 21 (2012)
In this research paper we reflects and analyzes, as the implementation of management policies and guidelines based on quality standards, safety and occupational health, environment, social responsibility and safety in food production; separately it has not yielded results in favor of corporate investors, employees, community, suppliers and customers. The results obtained indicate that the SSG: 21 system includes integrally these standards, including ethics and social responsibility as common factors in all activities. By implementing and maintaining these measures is expected to achieve reorientation of public and private companies, giving confidence to all stakeholders generating improved productivity and competitiveness at the global level.